The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1159/000081392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Simultaneous Determination of Tumor Markers in Fluid and Serum and Their Ratio in the Differential Diagnosis of Serous Effusions

Abstract: We evaluated the diagnostic utility of simultaneous determination of 5 tumor markers, CEA, CA 125, CA 15-3, CA 19-9 and cytokeratin 19 (CYFRA 21-1), in fluid and serum from 101 patients, 52 with pleural effusion (22 malignant) and 49 patients with ascites (14 malignant). Tumor marker concentrations in fluid from patients with malignant effusions were significantly higher than those obtained in benign fluids or serum. However, there are two types of tumor markers: those released/secreted by normal mesothelia su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 19 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…With CYFRA21-1,, Porcel et al [8] sought high specificity (100%) and obtained a sensitivity of 25% with a cut-off point of 175 μg/L with positive likelihood ratio (LHR+) >9999 and negative likelihood ratio (LHR-) of 0.75, Cynowska et al [9] sought high sensitivity (90.9%) and obtained a specificity of 7.7% with a cut-off point of 3.3 μg/L with LHR+ of 0.98 and LHR- of 1.18; finally, Korczynski et al [10], seeking high diagnostic accuracy, obtained a sensitivity of 41.7% and a specificity of 92.1% with a cut-off point of 74.7 μg/L LHR+ of 5.28 and LHR- of 0.63. Likewise, cut-off points ranging between 6.5 and 275 μg/L have been proposed for CEA in order to obtain maximum specificity [2026]. …”
Section: Discussionmentioning
confidence: 99%
“…With CYFRA21-1,, Porcel et al [8] sought high specificity (100%) and obtained a sensitivity of 25% with a cut-off point of 175 μg/L with positive likelihood ratio (LHR+) >9999 and negative likelihood ratio (LHR-) of 0.75, Cynowska et al [9] sought high sensitivity (90.9%) and obtained a specificity of 7.7% with a cut-off point of 3.3 μg/L with LHR+ of 0.98 and LHR- of 1.18; finally, Korczynski et al [10], seeking high diagnostic accuracy, obtained a sensitivity of 41.7% and a specificity of 92.1% with a cut-off point of 74.7 μg/L LHR+ of 5.28 and LHR- of 0.63. Likewise, cut-off points ranging between 6.5 and 275 μg/L have been proposed for CEA in order to obtain maximum specificity [2026]. …”
Section: Discussionmentioning
confidence: 99%
“…Abnormal serum levels of CA 125 may be found in several benign and malignant diseases other than ovarian cancer [2, 46, 1322]. Despite these issues, CA 125 is used to differentiate benign from malignant pelvic masses and is used as a prognostic factor in the early diagnosis of recurrence or to assess response to treatment [1113, 15, 16, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal CA 125 serum levels can be found in malignancies of different origin including epithelial (endometrial, endocervix and lung cancer) and non-epithelial malignancies (lymphomas) [46, 1321]. Abnormal CA 125 serum levels may be also found in several benign diseases, mainly those with effusions, liver or renal failure and benign gynaecological conditions (ovarian cysts, myomas and endometriosis) [4, 6, 1322]. Sensitivity of CA 125 in ovarian cancer is related to tumour stage, with abnormal CA 125 serum levels in approximately 50% of stage I patients and 80–90% in patients of stages III–IV [2, 46, 1116].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study using this strategy we found similar sensitivities for CEA, CA15-3, CA19-9 and Cancer antigen 72-4 (CA72-4) in pleural effusion (20). This strategy is less accurate for tumor markers secreted by mesothelial cells, such as cancer antigen 125 (CA125) and cytokeratin 19 fragments (CYFRA 21-1) that are best interpreted with a single determination in fluid effusion (21,22).…”
mentioning
confidence: 86%